PENGARUH PROFITABILITAS, CURRENT RATIO, LEVERAGE, FIRM SIZE TERHADAP EFFECTIVE TAX RATE DAN NILAI PERUSAHAAN - Natalia Kristiani Turnip, 11.05.52.0012; Indarti, Mg. Kentris (Students Journal of Accounting and Banking, 2015)
The study examines the effect of profitability, current ratio, leverage and firm size on effective tax rate and firm value. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis.The sampling method used purposive sampling with the observation period from 2009 to 2012. This study is free from the normality test and the classical assumption test. These result showed that profitability has a positive and not significant impact on effective tax rate. Current ratio and leverage has a negative and not significant impact on effective tax rate. Firm size has a negative and significant impact on effective tax rate. Profitability and firm size has a positive and significant impact on firm value. Current ratio has a negative and not signficant impact on firm value. The latest results show that leverage and effective tax rate has a positive and not significant impact on firm value.Keywords: Firm Value, Effective Tax Rate, Profitability, Current Ratio, Leverage, and Firm Size